Faktor-faktor yang Mempengaruhi Dividend Policy pada Perusahaan Sektor Infrastruktur, Utilitas, dan Transportasi - Ega Darmawati; Farida Titik Kristanti (Universitas Batanghari, 2022)
This study looks at the influence of corporate governance and liquidity on dividend policy in utilities, infrastructure and transportation sector companies listed on the Indonesia Stock Exchange in 2018-2020. Corporate governance plays a role in protecting the interests of business people in the company related to dividends. This study uses secondary data with purposive sampling technique and produces 14 companies with 42 research data. Descriptive analysis methods and panel data regression analysis are used because they are the most appropriate data analysis methods for testing quantitative data in this study. The results showed that the variables simultaneously had a significant effect on the dependent variable. The ownership structure variable partially has a significant positive effect on the dependent variable, while the other variables partially have no significant effect on dividend policy. It is suggested to increase the research by using variables outside this research such as company risk, cash flow and agency cost.